2018
DOI: 10.3389/fneur.2018.00386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhythmic Auditory Cueing in Gait Rehabilitation for Multiple Sclerosis: A Mini Systematic Review and Meta-Analysis

Abstract: Rhythmic auditory cueing has been shown to enhance gait performance in several movement disorders. The “entrainment effect” generated by the stimulations can enhance auditory motor coupling and instigate plasticity. However, a consensus as to its influence over gait training among patients with multiple sclerosis is still warranted. A systematic review and meta-analysis was carried out to analyze the effects of rhythmic auditory cueing in studies gait performance in patients with multiple sclerosis. This syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 141 publications
1
23
0
8
Order By: Relevance
“…Several of the systematic reviews and meta-analyses have also suggested a similar temporal course for auditory-motor training regimens to allow enhancements in motor performance. [29][30][31][32][33][34] In the present research, we aim to address the limitations of the experimental design used, and also to elucidate the influence of auditory feedback on motor learning. An expanded intermodal auditoryproprioceptive training protocol has been developed to investigate the efficacy of real-time auditory information on proprioceptive motor learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the systematic reviews and meta-analyses have also suggested a similar temporal course for auditory-motor training regimens to allow enhancements in motor performance. [29][30][31][32][33][34] In the present research, we aim to address the limitations of the experimental design used, and also to elucidate the influence of auditory feedback on motor learning. An expanded intermodal auditoryproprioceptive training protocol has been developed to investigate the efficacy of real-time auditory information on proprioceptive motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…reported functional neuroplastic changes (higher positive peak (P2) activity and β‐band oscillation) with a prolonged auditory–motor training session (30 min). Several of the systematic reviews and meta‐analyses have also suggested a similar temporal course for auditory–motor training regimens to allow enhancements in motor performance …”
Section: Introductionmentioning
confidence: 99%
“…The authors mentioned that this increased activation in the ipsilesional somatosensory cortex could have also resulted in unmasking of preexisting inactive motor representations, which then could have allowed enhancements in gait performance. [101][102][103][104][105][106] Conventionally, faster gait speed in stroke patients has been associated with improved kinematics and patterns of muscle activation. Lamontagne and Fung 107 reported that an increase in gait speed is attributable to larger STpLs and shorter cycle durations on the paretic and nonparetic sides, regardless of the functioning level.…”
Section: Discussionmentioning
confidence: 99%
“…Such type of an intervention involves mapping of movement parameters on the sound components, such as pitch, amplitude with a very minimal or no latency (72) [for differential effects of auditory cueing and sonification please see (82)]. Recent systematic reviews and meta-analyses have conclusively demonstrated the benefits of these auditory stimulations on gait and postural stability with aging (77), in neurological disorders such as stroke (82, 83, 86), parkinsonism (78), cerebral palsy (80), and multiple sclerosis (81). Findings from these reviews can have widespread implications for counteracting neurotoxicity related motor deficits in cancer patients.…”
Section: Prospective Role Of Music-based Therapies: External Auditorymentioning
confidence: 99%
“…Additionally, we also presume that damage induced by white matter deficits, which are a prominent manifestation of neurotoxicity can also be supplemented by the application of auditory stimulations (32, 87). Ghai and Ghai (81) recently demonstrated the beneficial effects of auditory cueing on patients with multiple sclerosis (a multifocal white matter disease). The authors stated evidence which supports the possibility of white matter re-organization with auditory-motor training [see (88)].…”
Section: Prospective Role Of Music-based Therapies: External Auditorymentioning
confidence: 99%